PRIORITY AREAS OF STATE REGULATION OF THE GAS INDUSTRY OF UKRAINE - Ulianchenko , Y. (Theory and Practice of Public Administration, 2021)
The article examines the priority areas of state regulation of the gas industry in Ukraine. Currently, the Ukrainian natural gas market is experiencing structural imbalances caused by imperfect state regulation of the industry. In addition to the current regulatory problems, the gas industry faces new challenges due to changes in the raw material base. This paper examines the main directions of improving the efficiency of state regulation in the gas industry, which counteract negative trends. We also developed scientifically based recommendations for improving the competitiveness of the Ukrainian gas industry through state regulation methods. The overall technological process is decomposed into the main business segments and mechanisms for improving their activities are proposed. As a result of the analysis, scientific and practical approaches to improving the competitiveness of the gas industry were developed. The results of the work can be used in the development of state programs to improve the competitiveness of the gas industry.The use of recommendations developed in this paper to improve the efficiency of state regulation of certain segments of the Ukrainian gas industry contributes to the growth of competitiveness not only of the gas industry or fuel and energy complex, but also of the national economy as a whole. The large share of the gas industry in the national gross domestic product makes it necessary to maintain and improve the efficiency of this segment.It is difficult to overestimate the role of the state in the process of improving the competitiveness of the Ukrainian gas industry. The main provisions of this article can be used both for further research in this direction and directly in National Economic Policy.The application of the measures developed in the article will not give a full-fledged result without improving discipline in paying for natural gas. Improvement of this area is possible by assessing the feasibility of natural gas supplies on pre-payment terms, introducing a system of fines for late payment of delivered volumes of natural gas, and stopping gas supplies to systemic defaulters when a certain debt accumulates.Further developments are needed both to identify specific mechanisms for implementing the state regulation measures proposed in the work, and to improve the payment discipline of gas consumers.